PEMBERDAYAAN MASYARAKAT MELALUI KELOMPOK PUSAT PELATIHAN PERTANIAN DAN PEDESAAN SWADAYA (P4S) “MERI REJEKI” DESA REJOSOPINGGIR - Arimurti Kriswibowo; Madania Uki Anindita; Isna Yunita Sari; Rofiah Inggil Pangestu (Journal Publicuho, 2021)
Community Empowerment in Rejosopinggir Village, Tembelang District, Jombang Regency by the Meri Rejeki Self-Supporter Farmer’s Agriculture and Rural Training Center (FAR-TC) group is currently in the spotlight. This self-help group was the representative of East Java Province in the National Agribusiness competition. The existence of the Meri Rejeki FAR-TC group was motivated by the strong desire of the Rejosopinggir village community, especially breeders, to improve the economy. The Meri Rejeki FAR-TC is expected to be able to directly play an active role in development through human resource development in the form of training and apprenticeship for farmers and breeders and the community in Rejosopinggir Village. The purpose of this study was to determine how the community empowerment process carried out by the Meri Rejeki FAR-TC group to the community of Rejosopinggir village. Community empowerment carried out by the Meri Rejeki FAR-TC is measured using the empowerment model according to D. Geroy (1998: 57-65), where there are 3 empowerment model strategies, including: 1) coaching or mentoring, 2) modeling, and 3) career. This research uses qualitative research methods, descriptive. The results of this study indicate that the Meri Rejeki FAR-TC group has succeeded in empowering the community, especially the residents of Rejosopinggir Village, Tembelang District, Jombang Regency.